Innovative teaching method—LEGO duplo in STEM education - Sütő Éva; Revákné Markóczi Ibolya (ЗУІ ім. Ференца Ракоці ІІ, 2025)
Abstract. In recent decades, science, technology, engineering and mathematics (STEM) education has gained increasing attention worldwide. Educational policy makers have recognized that future economic and social development is closely linked to the quality of skills and knowledge acquired in STEM fields. It is of paramount importance that STEM education is integrated into the curriculum from early childhood, as this period plays a key role in the development of children’s scientific interest and problemsolving skills [2]. The use of LEGO Duplo in STEM education can serve as an effective tool for the experiential acquisition of scientific knowledge [1]. The aim of this research is to examine the impact of integrating LEGO Duplo into education on the development of students’ conceptual knowledge about water. We paid special attention to the extent to which LEGO Duplo helps students expand their concepts related to water and recognize cause-and-effect relationships. During the study, we used one of the frequently used methods of impact measurement, the word association technique. The research took place in two stages: after completing the pretest, the experimental group participated in a LEGO-based session, while we organized a drawing session for the control group. The students interactively marked where and in what form they considered the presence of water in the urban environment to be important using droplets on cityscape elements. The responses were recorded in writing and on audio recordings. After analyzing the audio recordings, the concepts formulated by the students were documented individually in a Microsoft Excel spreadsheet program.
Keywords: LEGO Duplo; STEM education